In-depth analysis of tax reforms using the EUROMOD microsimulation model - Fidel Picos; Marie-Luise Schmitz (European Commission, Joint Research Centre (JRC), 2016)
In the aftermath of the financial and sovereign debt crisis, the need for a better understanding of the fiscal and equity implications of national tax policy reforms is greater than ever. National fiscal policies have a significant share in paving the way for economic recovery, fiscal consolidation and reducing looming inequality problems. The present work sets out a consistent framework for the in-depth country analyses of tax reforms using EUROMOD performed by the European Commission services in the context of the European Semester. Three examples of policy analysis are presented with the focus being on the provision of correct inferences alongside the typically analysed estimates and indicators.
Keywords: H23; H24; H53; C83; 330; Fiscal policy analysis; European Semester; survey data; microsimulation; variance estimation